LEGAL PROTECTION FOR CHILDREN AGAINST EARLY MARRIAGE - Nurhafni Nurhafni; Rahmiati Rahmiati; Gandung Sulistio Nugroho; Airi Safrijal (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
ABSTRACTThis study aims to analyze the urgency of legal protection for children against early marriage practices within the jurisdiction of the Mahkamah Syar'iyah Banda Aceh. Although the Marriage Law has established a minimum age limit of 19 years, the phenomenon of marriage dispensation continues to occur with various complex backgrounds. Utilizing an empirical juridical research method, this study examines the implementation of law in society through statutory and case approaches. The results indicate six primary determinants driving early marriage: economic factors, low education levels, parental influence, matchmaking practices, social environmental pressure, and personal factors or free association. Judges at the Mahkamah Syar'iyah Banda Aceh grant dispensation requests based on considerations of humanity, safety of life, educational continuity, and protection of offspring. Legal protection for children in this context refers to the guarantee of human rights to marry of free will without coercion as regulated in Article 10 paragraph (2) of the Human Rights Law, as well as preventive efforts through the collective responsibility of families and the government.